2021
DOI: 10.1016/j.aohep.2021.100468
|View full text |Cite
|
Sign up to set email alerts
|

P-108 Coronavirus Disease (Covid-19) in Liver Transplant Patients: A Single Center Experience in Bogotá Colombia

Abstract: Introduction On January 30th of 2020, the WHO declared the COVID-19 outbreak a health emergency. In Colombia the first case was reported on March 6th of 2020. The disease has unfavorable outcomes and mortality in patients with high risk factors like solid-organ transplant recipients. In Colombia the data of the behavior disease in liver transplant patients are limited. Objectives To describe the prevalence, need of admission to hospital, complications and mortality of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A study from Germany, conducted among 219 LT patients reported 3.1% confirmed cases of Covid-19 [14]. Another Colombian study of 540 liver transplant recipient, found positive Covid-19 infections in 6.2% of cases [15]. To mention that, when compared with the general population, LT patients were considered at higher risk for Covid-19 disease.…”
Section: Discussionmentioning
confidence: 99%
“…A study from Germany, conducted among 219 LT patients reported 3.1% confirmed cases of Covid-19 [14]. Another Colombian study of 540 liver transplant recipient, found positive Covid-19 infections in 6.2% of cases [15]. To mention that, when compared with the general population, LT patients were considered at higher risk for Covid-19 disease.…”
Section: Discussionmentioning
confidence: 99%